Study on the dynamic numerical analysis method for the settlement of flexible pavement (Rudarsko-geološko-naftni zbornik, 2019)
In view of the problems of a single parameter of rock and soil materials, unclear boundary simulation and a simplified dynamic load in the current calculation of pavement settlement, the stochastic finite element-infinite element coupling method was adopted in this study to simulate the roadbed of rock and soil, with a dynamic response analysis and a flex- ible pavement settlement calculation of roadbed were carried out under stochastic dynamic load. Discrete methods and dynamic stochastic finite element formulas for rock and soil random fields were particularly dealt with in this study. The results show that the method to stimulate roadbed is true with high calculation accuracy and strong engineering guiding significance. The displacement of flexible ground at any depth can be obtained by calculating the settlement of flexible pavement with the aid of the Matlab computer program.